Cartographic demonstration of the potential of ecotourism development in Penjwen district - مارف, د. شه‌ماڵ علی مارف; توفیق, د. كامران محمد توفيق; محمد, م. آرام حسن محمد (Sulaimani Journal for Humanities, 2025)
This study was conducted to represent the potential of ecotourism in Penjwen district and demonstrate it using Geographic Information System (GIS) techniques on a map، the purpose of highlighting the places in the study area that have high tourism value، in order to support In the efforts of sustainable tourism planning، Penjwen district has attractive natural characteristics، in terms of topographical and climatic diversity، which makes it an ideal environment for eco-tourism. The research includes three main sections، the first section is devoted to the theoretical framework of the research، in which the research area and concepts used are introduced، the second section is the most important capabilities of ecotourism development in Penjwen district The third section is devoted to analyzing the results of the survey form on the development of ecotourism in the study area The assumption of the richness of Penjwen district is based on the potential of eco-tourism development، while seeking to answer the question of whether these potentials play a role in the development of eco-tourism is there or not In order to achieve the expected results، the study used descriptive and analytical methods. The results of the study showed that Penjwen district has a high potential for eco-tourism and due to the lack of services in general and weak tourism services in particular، these potentials have not been used scientifically Develop sustainable tourism in the region through the use of eco-tourism potential، with the aim of making tourism an economic source of income for the residents of the region and play a role in its diversification Sources of income in Penjwen district.
Keywords: Ecotourism Tourism Development Sustainable Development Cartographic representation